Determination of Germanium with Phenylfluorone by β-Correction Sectrophotometry - Zhang, Peng-Fei; Gao, Hong-Wen; Shen, Nai-Kui (Asian Journal of Chemistry, 2010)
The determination of trace amount of germanium with phenylfIuorone using β-correction new spectrophotometry was studied. At pH 4.5, the germanium complex exhibits an absorption maximum at 540 nm, whereas that of the reagent is at 510 nm. Beer's law was obeyed over the concentrationrange of 0-12.5 μg of germanium per 25 mL of final solution.The method has been applied to the determination of trace amount ofgermanium in water and coal with satisfactory results.